Cardiac Energetics Before, During, and After Anthracycline-Based Chemotherapy in Breast Cancer Patients Using 31P Magnetic Resonance Spectroscopy: A Pilot Study - Macnaught, Gillian; Oikonomidou, Olga; Rodgers, Christopher T.; Clarke, William; Cooper, Annette; McVicars, Heather; Hayward, Larry; Mirsadraee, Saeed; Semple, Scott; Denvir, Martin A. (Frontiers in Cardiovascular Medicine, 2021)
This study explored the utility of phosphorus magnetic resonance spectroscopy (31P MRS) in identifying anthracycline-induced cardiac toxicity in patients with breast cancer. 20 patients with newly diagnosed breast cancer receiving anthracycline-based chemotherapy had cardiac magnetic resonance assessment of left ventricular ejection fraction (LVEF) and 31P MRS to determine myocardial Phosphocreatine/Adenosine Triphosphate ratio (PCr/ATP) at three time points: pre, mid and end-chemotherapy. Plasma high sensitivity cardiac troponin-I (cTn-I) tests and electrocardiograms were also performed at these same time points. PCr/ATP ratio did not change significantly between pre- and mid-chemo (2.16±0.46 v 2.00±0.56, p=0.80) and pre- and end-chemo (2.16±0.46 v 2.17±0.86, p=0.99). Mean LVEF reduced significantly by 5.1% between pre- and end-chemo (61.4±4.4 vs 56.3±8.1 %, p=0.02). Change in PCr/ATP ratios from pre- to end-chemo correlated inversely with changes in LVEF over the same period (r=-0.65, p=0.006). Plasma cTn-I increased progressively during chemotherapy from pre- to mid-chemo (1.35±0.81 to 4.40±2.64 ng/L; p=0.01) and from mid to end-chemo (4.40±2.64 to 18.33±13.23 ng/L; p=0.001). In this small cohort pilot study, we did not observe a clear change in mean PCr/ATP values during chemotherapy despite evidence of increased plasma cardiac biomarkers and reduced LVEF. Future similar studies should be adequately powered to take account of patient drop-out and variable changes in PCr/ATP.